2022
DOI: 10.1109/tcomm.2022.3211068
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Massive MIMO Meets OTFS Modulation

Abstract: We provide the first-ever performance evaluation of orthogonal time frequency space (OTFS) modulation in cellfree massive multiple-input multiple-output (MIMO) systems. To investigate the trade-off between performance and overhead, we apply embedded pilot-aided and superimposed pilot-based channel estimation methods. We then derive a closed-form expression for the individual user downlink and uplink spectral efficiencies (SEs) as a function of the numbers of APs, users and delay-Doppler domain channel estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Let us consider a P -path time-varying multi-path Rayleigh fading channel, whose channel impulse response (CIR) between the n t th TA and n r th RA is expressed as [17], [18] h nr,nt (τ, ν)…”
Section: S(nmentioning
confidence: 99%
“…Let us consider a P -path time-varying multi-path Rayleigh fading channel, whose channel impulse response (CIR) between the n t th TA and n r th RA is expressed as [17], [18] h nr,nt (τ, ν)…”
Section: S(nmentioning
confidence: 99%
“…To support the ever-evolving means of mobility in various fields of land, sea, and air, various new physical layer (PHY) technologies need to be developed for 6G, including the development of transmission and reception methods that enable communication at speeds exceeding 500 km/h, new communication methods to enable many users to conduct high-capacity communication, and methods to achieve lower latency and more reliable communication (e.g., non-orthogonal multiple access (NOMA) [18], [19], [20], in-band full-duplex (IBFD) [21], [22], [23], and new waveforms [24], [25], [26], [27], [28]). However, many studies have been limited to numerical and simulation evaluations based on theoretical formulas or computer simulations, and there are significant barriers to actual device demonstrations.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been conducted in the related field of MIMO-OTFS systems. For example, in [15], [16], the authors showed the tradeoff between the system performance and the signaling overhead for a cell-free massive MIMO system with OTFS modulation. In [17], the authors provided a channel estimation method for massive MIMO with OTFS transmissions.…”
Section: Introductionmentioning
confidence: 99%